Risk-Sharing Externalities - Bocola, Luigi; Lorenzoni, Guido (Journal of Political Economy, 2023)
Financial crises typically occur because firms and financial institutions are highly exposed to aggregate shocks. We propose a theory to explain these exposures. We study a model where entrepreneurs can issue state-contingent claims to consumers. Even though entrepreneurs can use these instruments to hedge negative shocks, they do not necessarily do so because insuring against these shocks is expensive, as consumers are also harmed by them. This effect is self-reinforcing because riskier balance sheets for entrepreneurs imply higher income volatility for the consumers, making insurance more costly in equilibrium. We show that this feedback is quantitatively important and leads to inefficiently high risk exposure for entrepreneurs.